ENVIRONMENTAL AWARENESS OF UNIVERSITY STUDENTS - Pavliukh, Lesia (Proceedings of National Aviation University, 2014)
The article is dedicated to environmental education of university students. It considers the algorithm thathelps to improve environmental skills acquired in the current system of higher education.